Boron and Beryllium Minerals in Granulite-facies Pegmatites and Implications of Beryllium Pegmatites for the Origin and Evolution of the Archean Napier Complex of East Antarctica - Grew, Edward S. (1998)
P(論文) CERNY included in his "abyssal class" those pegmatites originating by partial melting under granulite-facies conditions. Enrichment of abyssal pegmatites in rare elements such as Li, Be, B, Rb, and Cs is exceptional. Consequently, the presence of B minerals in pegmatites in granulite-facies rocks at Cape Andrahomana, SE Madagascar; in Rogaland, SW Norway; at Homagama, Sri Lanka; and in the Larsemann Hills, East Antarctica, have considerable geochemical interest. The host rocks are Al-rich paragneisses containing cordierite, almandine-pyrope, and sillimanite. The suite of B minerals is distinct from that in pegmatites associated with amphibolite-facies terrains in that tourmaline is not always present; instead, three phases related to sillimanite (grandidierite, werdingite, and boralsilite), dumortierite and prismatine are characteristic. Boron enrichment results from remobilization of B present in the host rock. Hence, the B pegmatites have retained the B signature characteristic of pelitic rocks, which is typically lost during granulite-facies metamorphism. Abyssal pegmatites containing Be minerals are found in the Archean Napier Complex at two localities in Casey Bay, Enderby Land, East Antarctica. The Be silicates surinamite and beryllian sapphirine, and the Be oxides chrysoberyl and musgravite are present instead of beryl. The host rocks are Mg-Al-rich gneisses containing sapphirine. The Be pegmatites were emplaced on the prograde path of increasing pressure and temperature and recrystallized under ultra-high-temperature conditions during a single deformational-metamorphic episode at 2475±25Ma. Be could have originated in the Mg-Al-rich host rocks inasmuch as Be concentrations are reported from Mg-Al-rich rocks elsewhere in the Napier Complex and at other localities worldwide. This scenario for the Late Archean event does not require the prolonged (400Ma) residence at depth proposed by other investigators; it is consistent with HENSEN's and MOTOYOSHI's model of insertion of anorthositic rocks above ...